Strengthening the Values of Honesty and Simplicity in Elementary School Children as Anti-Corruption Role Models - Sakban, Abdul; Budimansyah, Dasim; Darmawan, Cecep; Syaifullah, Syaifullah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
Corruption damages the development of society, so proactive steps are needed to foster integrity from an early age. This study investigates the effectiveness of reinforcing the values of honesty and modesty in elementary school children as anti-corruption role models. The research employed a mixed-methods approach across five schools. Data collection included pre- and post-intervention surveys, behavioral observations, and qualitative interviews with teachers, parents, and students. The findings reveal that curriculum integration, role modeling, and experiential learning significantly enhanced students’ ethical awareness and behaviors. Honesty was reinforced through storytelling and discussions, while simplicity was promoted via community service and creative activities. Quantitative analysis indicated a 25% improvement in honesty-related behaviors and an 18% increase in attitudes favoring simplicity. Parental involvement further amplified these outcomes, creating a cohesive framework for value reinforcement. This study provides a novel contribution by integrating simplicity as an anti-corruption value, addressing materialism as a root cause of unethical behavior. The framework’s success underscores the potential of early education in shaping ethical behaviors, offering valuable insights for policymakers, educators, and researchers. Future research could explore culturally adapted strategies and technological enhancements to optimize impact.